PELATIHAN PEMBUATAN MASKER REUSABLE BERBAHAN DASAR KAIN PERCA UNTUK MENCIPTAKAN PELUANG USAHA IRT DI DESA KLUMPANG KAMPUNG GG. MAWAR - Revika Ananda Putri; Fira Febriyanti; Nofri Agnesita Sitanggang; Itika Purnama Sari; Rohni Sari Panjaitan; Anita Tambunan; Emauela Dhea Carrosicca Ginting; Angela Helen Valentine Siagian; Nadila Syahputri; Adeline Fedorova Rahman Simalongo; Trisnawati Hutagalung (Universitas Negeri Medan, 2021)
Abstract The purpose of this activity is to help empower rural communities, especially IRT and utilize patchwork waste by making it a reusable mask and can improve IRT skills and help overcome poverty problems by holding training on making reusable masks by utilizing patchwork waste in Klumpang Village, Gg. Mawar, as well as improving the welfare of the Klumpang village community, especially IRT through production management and promoting it as a distinctive cultural fabric in Indonesia. The method that will be carried out in this activity is the Mentoring and Empowerment method. The method of delivering material during empowerment and mentoring uses the lecture method, question and answer and discussion. The results of community service activities can be seen in the activities carried out by the implementing team to partners, namely first, carrying out sewing technique training for housewives. Second, assisting villages in cultivating the available potential in order to build and create business opportunities for housewives in the midst of the current pandemic. Third, assisting the village community, namely housewives, in building a business platform and providing knowledge in tips for becoming an entrepreneur so that the product can be marketed and can increase the income of each housewife's family involved in the implementation of community service.